INISIATIF MASYARAKAT TERHADAP PEMANFAATAN HUTAN DESA MIRE KECAMATAN ULUBONGKA KABUPATEN TOJO UNA-UNA - Salma, Salma; Umar, Syukur (Jurnal Warta Rimba, 2020)
A village forest is a state forest not saddled with permission or rights, managed by the village and used for the welfare of the village. The village forest of Mire is located in Ulubongka District area , Tojo Una-una Regency, Central Sulawesi Province. The road facilities are connecting to Mire Village with other villages in Ulubongka District especially hill area has not been adequate with a means of transportation that has not been fully supported, as of access to local communities with other areas is limited both in the process of mobilizing the population and other access. These conditions are what influence society in both cultural social aspects and the economic development of production at village levels. The research was carried out in November through December 2019 using qualitative descretive methods. Data retrieval was done through surveys and interviews that included a list of questions. The research involved a personage especially the head of the family in Mire Village, Ulubangko District, Tojo Una-una Regency, Central Sulawesi. The result of the interview, have a lot of factors that bring out public initiative for utilization Mire Village Forest is Aleurites moluccana because it is not complicated for cultivation and we know for ourselves that the plant it a fast growing, the price was high. Their ecotourism development plans are tracking pathways to Mount Katopasa. But, on the other hand, the plan to manage the Mire Village Forest in the village doesn't compensated with enough knowledge of village forests and village management plan.Keywords: Forest Village, Utilization, Public Initiative